Design, synthesis and mode of action of novel 3‐chloro‐6‐pyrazolyl picolinate derivatives as herbicide candidates. Issue 5 (21st January 2021) - Yang, Zhikun; Li, Qibo; Yin, Jiaming; Liu, Ruiquan; Tian, Hao; Duan, Liusheng; Li, Zhaohu; Wang, Baomin; Tan, Weiming; Liu, Shangzhong
Abstract: BACKGROUND: Picolinate/picolinic acid compounds are an important class of synthetic auxin herbicides. To explore the herbicidal activity of 6‐pyrazolyl picolinate compounds, a series of 3‐chloro‐6‐pyrazolyl‐picolinate derivatives was designed and synthesized. RESULTS: Twenty‐five 3‐chloro‐6‐pyrazolyl‐picolinate derivatives synthesized were tested for herbicidal activity and the IC50 value of compound c5 to the growth of Arabidopsis thaliana root was 27 times lower than that of the commercial herbicide clopyralid. Compound c5 displayed better post‐emergence herbicidal activity and broader (Picloram, Clopyralid, Aminopyralid) herbicidal spectrum at a dosage of 400 g ha −1 in comparison with clopyralid; it also was safe to wheat and maize at this dosage. Arabidopsis thaliana phenotypes and expression of auxin‐response genes demonstrated that compound c5 might be a novel auxin‐type herbicide. Molecular docking analyses revealed that compound c5 had stronger binding ability to receptor AFB5 (auxin signaling F‐box protein 5) than clopyralid. CONCLUSION: These 6‐pyrazolyl picolinate compounds could be used as potential lead structures for the discovery of a novel synthetic auxin herbicide. © 2021 Society of Chemical Industry Abstract : The introduction of pyrazole is a successful strategy to improve the herbicidal activity of picolinate; 6‐pyrazolyl picolinate compounds could be used as lead structures for a novel synthetic auxin herbicide.